Method for energetic and economic analysis of buildings - Araújo, Catarina (2012)
Planet Earth is facing nowadays an environmental crisis without precedents. This is a matter of extreme importance and measures that allow reducing this problem have been discussed all over the world. One of the measures that have been appointed more often is the energy efficiency. In order to increase the energy efficiency, several technologies and legal documents have been developed. However, our society is facing, not only severe and unprecedented environmental crisis but also an economic crisis with similar magnitude. Therefore, it is of extreme importance to find methods that allow minimizing the environmental and economic impacts of the construction sector. The aim of this study is to find a method that allows the study of different measures relating their energy and economic performance.